2015
DOI: 10.1186/s13071-015-0775-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of orally administered fluralaner (BravectoTM) or topically applied imidacloprid/moxidectin (Advocate®) against generalized demodicosis in dogs

Abstract: BackgroundThis laboratory study compared the efficacy of Bravecto™ (fluralaner), formulated as a chewable tablet, with the efficacy of Advocate® (imidacloprid/moxidectin), formulated for topical administration, against naturally acquired generalized demodicosis in dogs.MethodsSixteen dogs, all diagnosed with generalized demodectic mange, were randomly allocated to two equal groups. Bravecto™ chewable tablets were administered once orally at a minimum dose of 25 mg fluralaner/kg body weight to one group of dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 24 publications
(29 reference statements)
12
93
0
1
Order By: Relevance
“…Fluralaner (Bravecto™) is effective against other cutaneous mite infestations of dogs including generalized demodicosis [15] and sarcoptic mange [16]. This is the first study showing efficacy of fluralaner treatment against a mite infestation of cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluralaner (Bravecto™) is effective against other cutaneous mite infestations of dogs including generalized demodicosis [15] and sarcoptic mange [16]. This is the first study showing efficacy of fluralaner treatment against a mite infestation of cats.…”
Section: Discussionmentioning
confidence: 99%
“…Oral fluralaner treatment is effective against generalized Demodex mite infestation on dogs [15] and oral and topical fluralaner treatment are effective against Sarcoptes scabei infestation on dogs [16], whereas there are no reports regarding efficacy against mites on cats. Fluralaner (Bravecto™) is commercially available as a chewable tablet for dogs or as a spot-on solution for cats.…”
Section: Introductionmentioning
confidence: 99%
“…Various therapeutic protocols are available for demodicosis and choosing the best treatment option will heavily rely on the individual dog. Recent studies have shown the novel isoxazoline antiparasitic agents, including afoxolaner (Nexgard, Merial) (Beugnet and others 2016) and fluralaner (Bravecto, Merck) (Fourie and others 2015), are an effective, safe and efficient treatment option for generalised demodicosis. Administration of these drugs for treatment of demodicosis is still considered off-label use, although due to proven efficacy and safety, afoxolaner (Nexgard, Merial) and fluralaner (Bravecto, Merck) are often recommended for dogs with demodicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Four months after initial examination, due to new drug availability, ivermectin was discontinued, and fluralaner (Bravecto, Merck) was prescribed for flea and tick prevention. Bravecto has been shown to effectively clear Demodex mite infestations with a single dose (Fourie and others 2015); therefore, this product offered the advantage of flea and tick prevention, as well as treatment of demodicosis. In comparison with ivermectin, the use of Bravecto for treatment of demodicosis can increase client compliance and has a lower risk of side effects.…”
Section: Treatmentmentioning
confidence: 99%
“…The results showed that after a single oral administration of fluralaner the mite numbers in skin scrapings were reduced by 99.8 per cent on day 28 and by 100 per cent on days 56 and 84. Mite numbers in the dogs treated with the spot-on product were reduced by 98 per cent on day 28, 96.5 per cent on day 56 and 94.7 per cent on day 84 (Fourie and others 2015). It is interesting to see that in this study monthly application of the spot-on product was as effective as only one dose of fluralaner so perhaps additional factors played a role in the successful treatment of these dogs.…”
Section: Treatmentmentioning
confidence: 99%